The Evaluation Program of Coaching Achievement on Women Futsal Athletes at Musi Rawas Sumatera Selatan - Ariko, Ariko; Hartono, Mugiyo; Nasuka, Nasuka (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
The Achievement problem stems from the Musi Rawas Women Futsal team's lack of achievement. The research aims are 1) to evalution the achievement of the development of futsal Achievement, 2) to evalutin the transaction of the development of futsal Achievement, 3) evalution the outcome of the Musi Rawas women futsal achievement development. Qualitative research with an evaluation approach is reviewed from Antecedent, Transaction, Outcome. Research in the Musi Rawas Women Futsal Team, Sumatra selatan for the 2019-2020 period. The team administrators, coaches, athletes, athletes' parents, and documentation of used as data sources for this research. Techniques for data collection was an observation, interview, and documentation. Analysis of the data was using data collection, data reduction, data display, conclusion . The findings of this study showed that the evalution of the Antecendent training program was conducted properly and in accordance with the management and coaching team's schedule. Evalution of athlete recruitment transactions is carried out openly. Recruitment of trainers selects a licensed trainer of at least level 1 national. The infrastructure is adequate, but the field's size does not satisfy international standards due to the field's ongoing renovation costs. The team was funded by State budget funds and the Musi Rawas Putri Futsal team. Musi Rawas Futsal team's performance in 5 team competitions resulted in a single victory in 2018. Conclusions from the assessment research conducted on the showed that additional changes to the training ground's size and evalution of the training program were required to achievement the champion target.